This isn’t the first time New Zealand has denied a citizen their passport - Belgrave D (The Spinoff, 2018)
Earlier this month the government cancelled the New Zealand passport of a woman living in Australia, citing classified security concerns. Stripping a NZ citizen of their passport might seem unprecedented – but it's happened before, writes David Belgrave.
Keywords: Citizenship; Passports; Security; New Zealand-Australia Relations